(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The working status of sanitary workers has remained almost unchanged for more than a century. They are facing some health threats because of their profession/occupation. The current study deals with occupational health threats faced by sanitary workers in Thoothukudi District. The study was conducted on the various occupational issues that sanitary workers face during working period based on the division of Thoothukudi District and selected Taluks. Together, primary data and secondary data were collected for data analysis. Primary data this is the firsthand information gathered through structure interview schedule, and the data were collected directly from the sanitary workers. Secondary data this is the second-hand information the data were collected from the journals, magazine, previous research reports and from the particulars website. The researcher wants directly to the sanitary workers and learned about the health problems faced by the sanitary workers. The stratified random sample was used to select the respondents to the samples for the primary data. The researcher has been selects a sample size 125 samples, which in Thoothukudi District, selects five divisions of Taluk areas. The statistical tools were applied to analyzed the data are percentage, rank, weighted average and chi square test.